Power Consumption of Liquid and Liquid/Solid Systems in a Rotating‐Drum Bioreactor. Issue 8 (5th July 2013) - Wang, Z.; Wen, S.; Zhang, Q.; Liu, G.; Wu, X.; Cong, W.
Abstract Rotating‐drum bioreactors combine the advantage of quiescent environment with mild shear stress for microbial growth. Power consumption is a vital parameter to evaluate the performance of reactors. To provide primary information for design and optimization of the rotating‐drum bioreactor, the effects of lifter arrangement conditions including number of lifters, lifter width and mounted angles, and operation conditions such as rotational speed, aeration rate, and solid volume fraction on power consumption were tested. Based on the experimental data, correlations for the power consumption of liquid and liquid/solid systems were proposed.